(untitled) (Revista Tempo e Argumento, 2017)
The Carandiru massacre, which took place in 1992, is characterized as a symbolic landmark in the history of the Brazilian penal system. The recollection of this past talks to issues like the dimension of what happened, impunity, the attempt to erase and shape memory, and the institution of massacre as a metaphor for new tragedies. In this process, we can observe the construction of two possible pasts: one undertaken by the State, establishing an official memory, and the other linked to various segments of organized civil society. I analyze the uses of this memory and its recollection strategies, and these categories are understood through the history of the present time and the public history. Keywords: Carandiru; Memory; Public History; History of the Present Time.